The Use of Blockchain Technology in Logistics and Supply Chain Management (SCM): A Systematic Review - Suzan Oguz; Gamze Alkan; Burcu Yilmaz; Ceren Kocabas (IEEE Access, 2024)
Today, logistics and supply chain management (SCM) are undergoing a major transformation due to the complexity of global supply networks, changing consumer demands and increasing competitive pressure. In this context, technological innovations are critical for the sectors to overcome these challenges. Blockchain technology stands out as an important digital innovation that has attracted attention in recent years with its potential to overcome many challenges in these sectors. Blockchain is considered as a technology that increases the security, transparency and efficiency of processes by accelerating digital transformation in the fields of logistics and SCM. The aim of this study, which is designed as systematic research, is to examine the effects of block chain technology on SCM and logistics, to evaluate the relevant literature by bibliometric analysis method and to identify existing research gaps. In this context, 1874 article studies in the relevant field were analyzed using the R program in accordance with the criteria determined. When the analyzed studies are evaluated in general, the advantages of transparency, reliability and efficiency provided by blockchain technology in supply chain processes come to the fore. In addition, the automated transaction capabilities of smart contracts reveal the potential to reduce costs and accelerate processes. Bibliometric analysis findings show that the most publications were made in 2023, the country with the most publications and citations was China, the journal with the most publications was Sustainability, and the institution with the most publications was Hong Kong Polytechnic University.